Time Analysis and Cost Estimation of Construction of Village Water Distribution Works For Clean Water Needs (Case Study of Tamangil Nuhuten Village, South Kei Besar Kec. Southeast Maluku Regency) - Paschal Rumihin; Andi Patriadi; Sajiyo Sajiyo (Pelopor Publikasi Akademika, 2025)
Water is a fundamental need for all living things, especially humans, to support survival. Tamangil Nuhuten Village, located in South Kei Besar Sub-district, Southeast Maluku Regency, faces great challenges in meeting the clean water needs of its residents. This study was conducted to evaluate the clean water distribution scheme through technical and economic approaches. The methods used included field surveys, water distribution simulation using EPANET 2.2 software, infrastructure development cost analysis, and a comprehensive assessment of construction time requirements. The results of the analysis show that the hilly topography of the village is the main obstacle in water distribution. To overcome this obstacle, a gravity-based distribution system is recommended. Based on EPANET 2.2 simulation, this system is able to fulfill the community's clean water needs efficiently. The total cost of building the distribution network is estimated at Rp8,202,383,000.00 with a construction time of six months. Furthermore, this research provides an in-depth analysis of the required time allocation for each construction phase to ensure project feasibility and efficiency. This research is expected to be a reference for the government and related parties in designing a water distribution system that is effective, sustainable, and in accordance with the needs of the Tamangil Nuhuten Village community.